2021
DOI: 10.1007/s42832-021-0084-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental fate and effects of organophosphate flame retardants in the soil-plant system

Abstract: Organophosphate flame retardants (OPFRs), as a replacement for polybrominated diphenyl ethers (PBDEs), are of increasing concern due to their high production over the years. Soil is the major environmental reservoir and interchange for OPFRs. OPFRs in soil could be transferred to the food chain, and pose potential ecological and human health risks. This review focused on the environmental fate and effects of typical OPFRs in the soil-plant system. We concluded that the sorption and transformation behaviors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 68 publications
1
2
0
Order By: Relevance
“…As compared with previous studies on the absorption, distribution, and biotransformation of OPEs in plants, , , we further found that the lateral root can be a major site for the accumulation of OPEs and the transport from the lateral root to the axial root can be a rate-limiting process for the acropetal translocation. Meanwhile, the biotransformation of OPEs in lateral root is also pronounced, which is likely associated with their high enzyme activity per unit area as compared with axial roots .…”
Section: Resultssupporting
confidence: 79%
“…As compared with previous studies on the absorption, distribution, and biotransformation of OPEs in plants, , , we further found that the lateral root can be a major site for the accumulation of OPEs and the transport from the lateral root to the axial root can be a rate-limiting process for the acropetal translocation. Meanwhile, the biotransformation of OPEs in lateral root is also pronounced, which is likely associated with their high enzyme activity per unit area as compared with axial roots .…”
Section: Resultssupporting
confidence: 79%
“…The low molecular weight PAHs below four rings mainly originated from petroleum pollution and the combustion of wood and coal in the low to medium temperature range, while the high molecular weight PAHs above four rings mainly originated from the high temperature combustion of fossil fuels [54]. In this study area, the concentration of PAHs above four rings was high.…”
Section: Composition Characteristicsmentioning
confidence: 77%
“…[ 84 ]. Common flame retardants such as organo-phosphate and brominated flame retardants (BFRs) [ 84 ] have long-term persistence in the soil and will undergo transformation, translocation, sorption, and root-uptake processes once in the environment [ 149 ]. They negatively affect public health and are toxic to the environment [ 84 ].…”
Section: Fate Environmental Hazard and Effects Of Contaminants In Bio...mentioning
confidence: 99%